PRINCIPLES OF PROFESSIONAL SELECTION ON THE BASIS OF PHYSIOLOGICAL CHARACTERISTICS OF A PERSON - Lуudmila V. Sorokina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the article the principles of professional selection based on professional characteristics are analysed. Professional selection is the choice of a specific person for the specific professional conditions. Professional selection aims not only to determine the presence of medical contraindications, but also to choose the profession of a person corresponding to a specific level of professional competence. The system of professional selection should be a "filter" that prevents the hiring of persons with physiological and psychological characteristics that do not meet the requirements of the appropriate technological processes and productions. The article describes the stages of professional selection (for medical reasons, according to the degree of professional suitability, the control stage). From the point of view of safety,the main directions of professional selection of the person (operator) can be taken: physiological, psychophysiological and professional direction. Each area in this case can set the features of quality assessment, which can be viewed and used separately or comprehensively. Every direction can have a number of properties, allowing to assess a person in a particular situation. The level of professional suitability is determined by the level of formation of professional competence (comprehensive assessment). Obtaining low level of formation of professional competence in the process of stage 1 of the professional selection, says that a student should be sent for retraining.